Domestic versus foreign drivers of trade (im)balances: How robust is evidence from estimated DSGE models - Roberta Cardani; Stefan Hohberger; Philipp Ludwig Pfeiffer; Lukas Vogel (Publications Office of the European Union, 2020)
Estimated DSGE models tend to ascribe a significant and often predominant part of a country's trade balance (TB) dynamics to domestic drivers ("shocks"), suggesting foreign factors to be only of secondary importance. This paper revisits the result based on more agnostic approaches to shock transmission and using "agnostic structural disturbances". We estimate multi-region models for Germany and Spain as countries with very distinct TB patterns since 1999. Results suggest that domestic drivers remain dominant when theory-based restrictions on shock transmission are relaxed, although the transmission of foreign shocks is strengthened.
Keywords: F30; F32; F41; F45; 330; Agnostic structural disturbances; open economy DSGE model; trade balance; Germany; Spain